Clinical application of indocyanine green fluorescence imaging navigation for pediatric renal cancer - Feng, Jun; Yang, Wei; Qin, Hong; Xu, Jiatong; Liu, Shan; Han, Jianyu; Li, Ning; He, Lejian; Wang, Huanmin (Frontiers in Pediatrics, 2023)
Background: Indocyanine Green (ICG) fluorescence imaging has been widely used in the surgical treatment of adult renal cancers, but its application in pediatric renal cancers has rarely been reported. This study aims to summarize the experience of ICG fluorescence imaging in pediatric renal cancers and explores its safety and feasibility. Methods: The clinical features, surgical information, ICG administration regimen, near infrared radiography data in vivo and ex vivo and pathological results of children with renal cancers using ICG navigation were analyzed and summarized. Results: There were 7 cases of renal cancer, including 4 cases of Wilms tumor (WT), 1 case of malignant rhabdoid tumor of the kidney (MRTK) and 2 cases of renal cell carcinoma (RCC). By intraoperative intravenous injection of ICG from 2.5 to 5 mg (0.05-0.67 mg/kg), the tumors were visualized in 6 cases in vivo or ex vivo, and the tumor visualization failed in 1 case due to renal artery embolization before operation. By injecting 5 mg ICG into the normal renal tissue during the operation, 3 patients achieved fluorescent localization of sentinel lymph nodes. No ICG-related adverse reactions were found in any of the patients during or after operation. Conclusions: ICG fluorescence imaging is safe and feasible for renal cancers in children. Intraoperative administration can achieve tumor and sentinel lymph node visualization which will facilitate the development of nephron sparing surgery (NSS). However, the technique is affected by ICG dose, anatomical conditions around the tumor, and renal blood flow. A proper dose of ICG and the complete removal of perirenal fat are helpful for the fluorescence imaging of the tumor. It has potential in the operation of renal cancer in children.